Fractional derivative on MHD flow of the third grade fluid in the porous tube subjected to a constant body acceleration and pressure gradient - Salah Uddin, Salah Uddin; Mohamad, Mahathir; Kamardan, M Ghazali; Sufahani, Suliadi Firdaus (Penerbit UTHM, 2018)
The third grade non-Newtonian MHD flow in the porous vertical tube subjected to a constant body acceleration and pressure gradient was studied using the time fractional derivative by employing the Laplace and the finite Hankel transforms. The Mathematica software was used to simulate the velocity profile and the Bessel functions with zero order and first order of first kind. The correlations between the flow velocity and the third grade nonNewtonian fluid parameter and the magnetic field were found to be negative